2016
DOI: 10.1016/j.mce.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Testing the critical window of estradiol replacement on gene expression of vasopressin, oxytocin, and their receptors, in the hypothalamus of aging female rats

Abstract: The current study tested the “critical window” hypothesis of menopause that postulates that the timing and duration of hormone treatment determine their potential outcomes. Our focus was genes in the rat hypothalamus involved in social and affiliative behaviors that change with aging and/or estradiol (E2): Avp, Avpr1a, Oxt, Oxtr, and Esr2 in the paraventricular nucleus (PVN) and supraoptic nucleus (SON). Rats were reproductively mature or aging adults, ovariectomized, given E2 or vehicle treatment of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…After reproductive senescence, there could be an adjustment in estrogen receptor sensitivity [ 44 , 45 , 46 ] that affects the critical period for an intervention with estrogens. Importantly, most studies perform OVX before periestropause and evaluate the critical window for intervention considering the period of estrogen decline [ 12 , 33 , 45 , 47 ], but not the age at which OVX is performed. In this sense, recently García et al [ 47 ] showed that changes in the expression of genes involved in social and affiliative behaviors—such as vasopressin and oxitocin—varied according to the age when OVX was performed as well as the interval after OVX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reproductive senescence, there could be an adjustment in estrogen receptor sensitivity [ 44 , 45 , 46 ] that affects the critical period for an intervention with estrogens. Importantly, most studies perform OVX before periestropause and evaluate the critical window for intervention considering the period of estrogen decline [ 12 , 33 , 45 , 47 ], but not the age at which OVX is performed. In this sense, recently García et al [ 47 ] showed that changes in the expression of genes involved in social and affiliative behaviors—such as vasopressin and oxitocin—varied according to the age when OVX was performed as well as the interval after OVX.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs were freshly prepared. The doses and latencies were chosen from previous studies [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tissue samples assayed in this study were previously generated and utilized for separate publications ( 15 , 16 ). This study utilized the cDNA generated by these previous publications.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing a reproductive aging female rat model ( 15 , 16 ), we sought to determine the impact of age and hormone treatment duration and timing on genes crucial for GnRH-(1–5) signaling, particularly in the medial preoptic area (mPOA) and arcuate nucleus (ARC) of the hypothalamus. The mPOA is of interest as GnRH cell bodies are mainly found here, and it is a major site for the regulation of reproductive function ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex (PFC), medial amygdala (MeA), bed nucleus of the stria terminalis (BNST) and the hypothalamus are among the estrogen-sensitive nodes of this neural circuit (Arimatsu and Hatanaka, 1986; Kugaya et al, 2003; Han and De Vries, 2003; Garcia et al, 2016). Considering their key roles and abundant expression of ERs (Kugaya et al, 2003; Walker et al, 2003; Saper et al, 2005), they are important targets of analysis for understanding potential neuromolecular substrates involved in estrogens’ regulation of social behavior.…”
Section: Introductionmentioning
confidence: 99%